The Moderating Effect of Loyalty on Incentive Schemes and Budgetary Slack Relationship: An Experimental Investigation - Rohma, Frida Fanani; Novitasari, Inge (The Indonesian Journal of Accounting Research, 2023)
This study examines the causal relationship between incentives scheme (subjective vs. objective) on budgetary slack. Besides, this study also identifies the moderating role of loyalty on the relationship between those two variables. This study used a 2 × 2 between-subjects laboratory experiment with 102 accounting undergraduate students as the subjects. Incentive schemes were manipulated into two types (subjective and objective), and loyalty was categorized into two (high and low). The results show that Budgetary slack tends to be higher under the subjective incentives scheme than the objective one. Also, loyalty negatively influences budgetary slack. Loyalty reduces the negative effect of incentives scheme and budgetary slack relationship. Individuals' loyalty, as one of the internal factors that encourage positive individual behavior, will result in lower slack even though they are faced with conditions that are not as desired.